Mutu Pelayanan Kesehatan Reproduksi Ramah Remaja sebagai Strategi Preventif Pernikahan Anak: Tinjauan Literatur - Dona Putri Ariningrum; Lusyta Puri Ardhiyanti (Indonesian Journal of Midwifery Scientific, 2026)
Adolescent reproductive health and child marriage remain global health problems influenced by limited access to health services, inadequate education, socio-cultural factors, and gender inequality. These conditions increase the risk of adolescent pregnancy, reproductive health disorders, and psychological problems. This literature review aimed to analyze the quality of adolescent-friendly reproductive health services and their role in preventing child marriage. The study used a systematic literature review method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were conducted through ScienceDirect, Google Scholar, PubMed, ResearchGate, and accredited national journals using keywords related to child marriage, adolescent reproductive health, and health service quality. Articles were selected using inclusion and exclusion criteria, resulting in 12 articles published between 2021–2026. The findings showed that the quality of reproductive health services is influenced by the quality of health workers, service systems, service accessibility, health education, family support, and socio-cultural and psychological factors. Programs such as PKPR, Generasi Berencana (GenRe), and reproductive health education were proven to improve adolescent knowledge and support child marriage prevention. The review concludes that strengthening the quality of adolescent reproductive health services is necessary as a preventive strategy to reduce child marriage rates. Keywords: Adolescent reproductive health; Child marriage; Early marriage; Health service quality; Youth health services